Vocabulary size and critical academic reading ability of secondary students in Sabah - Lee, Jocelyn Yee Vun; Wong, Alice Su Chu (Penerbit Universiti Kebangsaan Malaysia, 2020)
English Language Learners' or ELLs reading comprehension of a text is affected by many factors. One of which is vocabulary knowledge. Several studies have shown that there is a direct link between vocabulary and reading comprehension. Although in the present study, students' comprehension, personal response and critical reading abilities were assessed, only the critical reading component is reported in this paper. While sizable studies have examined students' comprehension skills, little is known about the critical reading ability of secondary students, an important factor in students' college academic success. The purpose of the current study was threefold: (a) to investigate ELL secondary students' vocabulary level, (b) to gauge their critical academic reading ability, and (c) to determine the relationship between these two variables. Eighty-five participants from a public school in Kota Kinabalu, Sabah participated in the study. Receptive vocabulary test and an academic critical reading test were administered. Results showed that the vocabulary size of the students was associated with their critical academic abilities. The findings have pedagogical implications for educators.